Hyperintensity of the Precentral Gyral Subcortical White Matter and Hypointensity of the Precentral Gyrus on Fluid-Attenuated Inversion Recovery: Variation with Age and Implications for the Diagnosis of Amyotrophic Lateral Sclerosis - Ngai, S.; Tang, Y.M.; Du, L.; Stuckey, S. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Hyperintensity of the subcortical white matter (SWM) of the precentral gyrus and hypointensity of the precentral gyrus gray matter (PGGM) on fluid-attenuated inversion recovery (FLAIR) are described as potentially useful diagnostic findings in amyotrophic lateral sclerosis (ALS). A detailed study of the prevalence of these findings in various age groups has not been described.METHODS: One hundred twenty-two patients underwent axial FLAIR brain examinations as part of either hearing loss or tinnitus evaluation. Examinations were randomly selected to reflect an even spread through the decades from ages 15 to 78 years and were reviewed by 2 readers, blinded to patient’s age and sex, for the presence/absence of the above 2 signs. If SWM hyperintensity was present, it was graded as intense as caudate nucleus (grade 1) or insula (grade 2).RESULTS: We identified 32 cases of grade 1 and 5 cases of grade 2 SWM hyperintensity, and 28 cases of PGGM hypointensity. Both signs showed significant Spearman correlation with increasing age (r = 0.55, P < .001 for grade 1, r = 0.45, P < .001 for grade 2 SWM hyperintensity, r = 0.45, P < .001 for PGGM hypointensity). Analysis of variance showed there was a significant difference between the different age groups (P < .001) for both signs. Grading of the SWM and PGGM signals were highly reproducible with very good interobserver agreement (r = 0.88, P < .001, and r = 0.97, P < .001, respectively).CONCLUSION: This study suggests a statistically significant relationship between increasing age and the frequency of precentral gyrus SWM hyperintensity and PGGM hypointensity on FLAIR, and reinforces previous reports that these signs can be seen in patients who do not have ALS.